How worthwhile is teleworking from a sustainable mobility perspective? The case of Brussels Capital region. - Lier, Tom van; Witte, Astrid de; Macharis, Cathy (European Journal of Transport and Infrastructure Research, 2014)
Since the 1960s, the number of commuters in the Brussels Capital Region has doubled: nowadays more than 400,000 workers commute in and out of Brussels on a daily basis. In order to preserve the liveability of the region in terms of mobility, environment and traffic safety, policy measures should be taken to reduce the number and/or distances of commuter trips. Telework is often suggested as an instrument to reduce the environmental and socio-economic impacts of mobility on society. Currently, the implementation of teleworking is however still rather limited and fragmental in most companies in Belgium. Goal of this paper is to assess whether further encouragement of telework is advisable from a sustainable mobility viewpoint. Based on Belgian survey data, an appraisal of the environmental and mobility related impacts of telework for companies located in the Brussels Capital Region is performed, using an analysis of the strengths, weaknesses, opportunities and threats of telework. In order to quantify the effects, external costs of trips to the central headquarter office are compared to those of trips to decentralized satellite offices and those caused by additional distances travelled when teleworking at home. Modal shifts occurring between trips travelled to the central office and trips travelled to the satellite office are taken into account and play an important role in the overall impact on external transport costs. Also receptor density and congestion levels along the routes travelled are taken into account.